The Aging of Iron Man - Ashraf, Azhaar; Clark, Maryam; So, Po-Wah (Frontiers in Aging Neuroscience, 2018)
Brain iron is tightly regulated by a multitude of proteins to ensure homeostasis. Iron dyshomeostasis has become a molecular signature associated with ageing which is accompanied by progressive decline in cognitive processes. A common theme in neurodegenerative diseases where age is the major risk factor, iron dyshomeostasis coincides with neuroinflammation, abnormal protein aggregation, neurodegeneration and neurobehavioral deficits. There is a great need to determine the mechanisms governing perturbations in iron metabolism, in particular to distinguish between physiological and pathological ageing to generate fruitful therapeutic targets for neurodegenerative diseases. The aim of the present review is to focus on the age-related alterations in brain iron metabolism from a cellular and molecular biology perspective, alongside genetics and neuroimaging aspects in man and rodent models, with respect to normal ageing and neurodegeneration. In particular, the relationship between iron dyshomeostasis and neuroinflammation will be evaluated, as well as the effects of systemic iron overload on the brain. Based on the evidence discussed here, we suggest a synergistic use of iron-chelators and anti-inflammatories as putative anti-brain ageing therapies to counteract pathological ageing in neurodegenerative diseases.